Pictorial Stories for Children: vol.24 - Compilation (chennai : Sri Ramakrishna Math, 2022)
Hindu mythological and didactic tales by various authors and illustrators
Bhagavannama Bodhendra, Offering to the Guru, The Greatness of Rama's Name.
Beautifully colorful Illustrated Children's Picture Books